ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI MUSIK UNTUK MANAJEMEN DELIRIUM PADA PASIEN DI RUANG INTENSIVE CARE UNIT RSUD TARAKAN - Sanaya Azizah Puteri (2022)
Delirium is an acute disfunction affecting consciousness and cognitive function. Delirium occurs frequently in patients treated in the intensive care unit (ICU). Prolonged ICU stay and mechanical ventilation use may occur in ventilated patients with delirium. Prevention and delirium management are required to avoid aforementioned complications. Management of delirium consists of both pharmalogical and non-pharmalogical approaches, one of which is music therapy intervention. Music therapy should be done within the first 24 hours critically ill patients admitted to the ICU. Slow-tempo music was used as it has similar effects to that of sedation which is increasing the interaction between two brain hemispheres and neurons. The nursing process analysis shows the effectiveness of music therapy intervention in management of delirium in critically ill patients in Tarakan Regional Hospital. Music therapy also helps in less exposure of the ICU patients to sedation. It is also important to acknowledge the role of pharmacological approaches done to reduce delirium which, in this case, is the use of sedation to reduce neurotransmitter dissociation and mechanical ventilator to supply oxygen to the brain.